The use of integrin binding domain loaded hydrogel (RGD) with minimally invasive surgical technique in treatment of periodontal intrabony defect: a randomized clinical and biochemical study - Shaimaa Hamdy ABD EL-AZEEM; Ahmed Abdallah KHALIL; Mohammed Abdel-Moniem IBRAHIM; Ahmed Y GAMAL (Journal of Applied Oral Science, 2023)
Abstract Periodontal regeneration faces multiple challenges, the most important being cellular insufficiency. In an attempt to improve defect cellularity, we aimed to demonstrate enhancing cellular attraction using arginine-glycine-aspartic acid (RGD) adhesion molecule legend blended hydrogel within the intrabony defects. Methodology Forty-five intrabony defects were selected from patients with stage III or IV - grade A or B periodontitis and divided randomly into three equal groups of 15 each: group1 (G1): received minimally invasive surgical technique (MIST) alone, group2 (G2): received MIST and placebo hydrogel injection, and group3 (G3): were treated with MIST and RGD hydrogel injection. Primary outcomes 6 months following therapy were; defect base fill (DBF) and defect width measurement (DW); secondary outcomes were clinical attachment level (CAL), pocket depth (PD), plaque index (PI), gingival index (GI), and biochemical analysis of bone morphogenetic protein (BMP-2) evaluated at 1,7,14 and 21 days following therapy. Results Significant improvements in DBF, CAL, and PD were observed in the three studied groups 6 months following therapy compared to baseline (p<0.05). A significant improvement in DBF was reported in G3 compared to G1 and 2 (p=0.005). Additionally, a significantly higher CAL gain was reported in G3 compared to that of G1 (p=0.02). Group 3 was associated with a significantly higher level of BMP-2 compared to G1 and G2 in all reported periods. Conclusion RGD peptide carried on a hydrogel delivery agent and contained with a minimally invasive flap could be a reliable option in improving the outcomes of periodontal therapy.